Protection of religious education in the message of the Białystok weekly titled "Zjednoczenie Katolickie" (1933-1935) - Grzegorz Michalski (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
Published in Białystok in 1933-1935, "Zjednoczenie Katolickie" (Catholic Union) was a Catholic weekly established by reverend Aleksander Chodyka. The analysis of the contents of that periodical shows that it not only discussed information on current events in Poland and abroad but also focused on issues related to the Church's doctrine and instruction. In this context, the authors have reconstructed inconsistencies and difficulties in the performance of religious education tasks presented by journalists, considering all described incidents related to those issues, regardless from the place of their occurrence in Poland: signs of negative attitude to faith of headmasters and teachers of teaching colleges, hostile references to the Church in schools in the Eastern and Western borderlands of Poland and in the Pomerania, attempts to restrict activities of students' religious organizations in Lviv and the Silesia, and reasons for objecting, by bishops, to decisions of state authorities concerning the reduction of the number of hours dedicated to religious instruction at schools.